Does Modern Democracy Represent the People? - Karalius, Gintas (Politologija, 2018)
[only abstract in English; full article, abstract in Lithuanian] The purpose of this article is to suggest an innovative theoretical approach to modern democracy and its implicit contradiction between the idea of public sovereignty and the model of political representation. The apparent practical problem arising from this contradiction is the lack of legitimacy in democratically elected officials and parliament in general. The article argues that the issue with democratic representation cannot be explained sociologically, but must include a theoretical analysis of the normative contradiction between the egalitarian principle of sovereignty of the people and the hierarchical model of political representation. The article develops its argument from the conceptual framework laid down in the political theory of Montesquieu. Montesquieu’s thoughts on political regimes offer important insights about modern representative democracy, highlighting the structural relationship between what he called the “nature of democracy” (the rule of the people) and the “generating principle of democracy” (love for equality). Three contemporary interpretations of Montesquieu’s theory (by Fred Dallmayr, Michael Mosher and Sharon Krause) are introduced and critically evaluated. The article concludes that: Representative democracy suffers from a structural tension between the democratic idea of the rule of the people and its practical implementation through the model of representation, which was inherited from predemocratic monarchic regimes. The problem is not sociological but structural. Montesquieu’s theory offers a conceptual framework for analyzing the inner tension of representative democracy between the ideas of egalitarianism and political hierarchy. Contemporary authors suggest different interpretations of Montesquieu’s thought and offer several strategies for the possible improvement of democratic rule, such as (1) redrawing the notion of representation, (2) creating a more empowered civic society and (3) introducing a meritocratic educational system for individuals. Yet, they all miss the original idea posed by the Enlightenment philosopher regarding the balance between the democratic principle (passion for equality) and its natural claim to represent the people with “intermediary institutions” that mitigate the adverse tendencies of the democratic form of government. Philosophical discussions about democratic legitimacy should consider one Montesquieu’s statement that is rarely theoretically acknowledged: that democratic political representation needs non-egalitarian social ideas. This means that democracy must tolerate certain non-democratic social ideas (such as honor) for its own benefit, because they provide the necessary balancing institutions. Such an idea would benefit the ongoing debates about democracy by providing a more structural outlook on the fundamental source of the problem (which is a structural collision of contradictory ideas: “equality” vs. “hierarchy”) than those offered by the sociological strategies of democratization or civic empowerment.